2021
DOI: 10.1002/jwmg.21998
|View full text |Cite
|
Sign up to set email alerts
|

Waif Gopher Tortoise Survival and Site Fidelity Following Translocation

Abstract: Gopher tortoises (Gopherus polyphemus) are among the most commonly translocated reptiles. Waif tortoises are animals frequently of unknown origin that have been displaced from the wild and often held in human possession for various reasons and durations. Although there are risks associated with any translocation, waif tortoises are generally excluded from translocation projects because of heightened concerns of introducing pathogens and uncertainty about the post-release survival of these individuals. If these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Some gopher tortoises translocated to a protected area because of development died of stress‐related starvation within the first 2 years; models indicated that deaths occurred at sites with higher densities of translocated tortoises (Cozad et al 2020). Long‐term analyses of survival of translocated captive gopher and Hermann's tortoises in protected areas was high: ≥0.90 annually for subadult and adult gopher after approximately 12 years (McKee et al 2021) and 0.978 after 14 years and 0.972 after 29 years for Hermann's tortoises (Bertolero et al 2007, 2018). Predators negatively affected success of translocations of gopher and Herman's tortoises (Ashton and Burke 2007, Bertolero et al 2007, Pille et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some gopher tortoises translocated to a protected area because of development died of stress‐related starvation within the first 2 years; models indicated that deaths occurred at sites with higher densities of translocated tortoises (Cozad et al 2020). Long‐term analyses of survival of translocated captive gopher and Hermann's tortoises in protected areas was high: ≥0.90 annually for subadult and adult gopher after approximately 12 years (McKee et al 2021) and 0.978 after 14 years and 0.972 after 29 years for Hermann's tortoises (Bertolero et al 2007, 2018). Predators negatively affected success of translocations of gopher and Herman's tortoises (Ashton and Burke 2007, Bertolero et al 2007, Pille et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Translocations may be more successful (in terms of reproductive output of translocated females) if tortoises are moved northward to track their climatic niche as the climate continues to warm. Northward translocations are already occurring (Cozad 2018, McKee et al 2021, although not as an intentional response to a changing climate, but as a function of where land is available. To understand how movement of tortoises among climates within the species' range will impact the long-term persistence of translocated populations, it will be important to determine whether the effects that we have reported on here (warming conditions leading to increases in reproductive output) translate to other populations from warmer climates.…”
Section: Discussionmentioning
confidence: 99%
“…The Gopher Tortoise has experienced significant population declines throughout its range (Hermann et al 2002) and is federally or state listed for protection within 6 states (Berry and Aresco 2014). As human-impacted areas have expanded and reduced Gopher Tortoise habitat, some populations remain in "island" pockets that can be small and/ or separated from other populations (McKee et al 2021). Understanding how threatened species, such as the Gopher Tortoise, respond in novel habitats, including urbanized environments, is important to determine their sustainability in different habitats and to reduce the likelihood of extirpation.…”
Section: Introductionmentioning
confidence: 99%